2020
DOI: 10.1002/onco.13523
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of Panitumumab Monotherapy in Chemotherapy-Naïve Frail or Elderly Patients with Unresectable RAS Wild-Type Colorectal Cancer: OGSG 1602

Abstract: Panitumumab monotherapy showed favorable efficacy and feasibility in the treatment of frail or elderly patients with RAS wild-type unresectable colorectal cancer.• It is especially effective for left-sided tumors; therefore, panitumumab as first-line treatment could be an additional therapeutic option for frail elderly patients, particularly in those who are unsuitable for upfront oxaliplatin-based or irinotecan-based combination regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…The TRAE profile of SCT200 was similar to that of other anti-EGFR monoclonal antibody therapies, such as cetuximab 31,32 , nimotuzumab 33 , and panitumumab [34][35][36] , for solid cancers. All TRAEs were predictable and manageable.…”
Section: Discussionmentioning
confidence: 67%
“…The TRAE profile of SCT200 was similar to that of other anti-EGFR monoclonal antibody therapies, such as cetuximab 31,32 , nimotuzumab 33 , and panitumumab [34][35][36] , for solid cancers. All TRAEs were predictable and manageable.…”
Section: Discussionmentioning
confidence: 67%
“…The Asian experts also accepted ‘recommendation 4l’ ( Table 1 ) unchanged ( 100% consensus ), supported by data from the Japanese phase II OGSG 1602 study (UMIN000024528) of panitumumab monotherapy in chemotherapy-naive frail/elderly patients with unresectable RAS wt metastatic/advanced CRC. 101 The LoE however, was revised to III , C ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is also possible that even if patients had Grade ≥ 3 CIN and could have continued panitumumab monotherapy while suspending FTD/TPI due to Grade ≥ 3 CIN, investigators may have decided to simply suspend both treatments; this would account for the low panitumumab RDI. Recently, it was reported that in heavily pre-treated patients (refractory to chemotherapy, anti-VEGF, and anti-EGFR therapy [for tumours with wild-type RAS ]) biweekly administration of FTD/TPI with bevacizumab showed promising anti-tumour activity with acceptable toxicity and dramatically decreased CIN compared with the standard combination treatment schedule [ 20 ]. Thus, if panitumumab was combined with biweekly FTD/TPI, it may be possible to decrease CIN and maintain the RDI of both drugs, although additional studies are required to explore this possibility.…”
Section: Discussionmentioning
confidence: 99%